The actin cytoskeleton and bacterial infection - Mannherz, Hans Georg (Springer, 2017)
This volume describes the mechanisms which bacteria have created to secure their survival, proliferation and dissemination by subverting the actin cytoskeleton of host cells. Bacteria have developed a veritable arsenal of toxins, effector proteins and virulence factors that allow them to modify the properties of the intracellular actin cytoskeleton for their own purposes. Bacterial factors either modify actin directly as the main component of this part of the cytoskeleton or functionally subvert regulatory or signalling proteins terminating at the actin cytoskeleton. In short, this volume provides an overview of the various tricks bacteria have evolved to ´act on actin´ in order to hijack this essential host cell component for their own needs. As such, it will be of interest to scientists from many fields, as well as clinicians whose work involves infectious diseases.
Keywords: Actin.; Cytoskeleton.; elektronické knihy; electronic books